A method for enhancing inorganic material-polymer interface connection strength

By forming a parallel covalent bond structure on the surface of inorganic materials, the problem of insufficient interface connection strength between inorganic materials and polymers is solved, and the interface connection strength is significantly improved and the stability under high stress environments is achieved.

CN116444177BActive Publication Date: 2025-01-24JILIN UNIVERSITY
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202310418473.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-04-19
Publication Date
2025-01-24
Estimated Expiration
2043-04-19

AI Technical Summary

Technical Problem

The lack of interfacial connection strength between inorganic materials and polymers leads to limited stability and application prospects of composite materials under stress and water-containing conditions.

Method used

Through the functionalization of inorganic materials and react with the dendritic molecules or branches-like molecules to form a parallel bonding structure, enhance the connection strength of the inorganic material-polymer interface.

Benefits of technology

It achieves a significant improvement in the interface connection strength, improves the overall connection strength through the stress dispersion effect, maintains a long silicon-oxygen bond life in a high-stress environment, and supports long-term single-molecule force spectroscopy testing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116444177B_ABST
    Figure CN116444177B_ABST
Patent Text Reader

Abstract

The present invention provides a method for enhancing the connection strength of an inorganic material-polymer interface, and belongs to the technical field of inorganic material surface treatment. The method comprises the following steps: functionalizing an inorganic material to obtain a functionalized inorganic material, wherein the functionalization is hydroxylation, carboxylation or epoxidation; reacting the functionalized inorganic material with a compound to form a parallel covalent bond, wherein the compound is a dendritic molecule or a branched molecule, and the reaction is an esterification reaction, an amidation reaction or an addition reaction. The present invention uses a parallel covalent bond to achieve inorganic material-polymer interface connection, which can improve the interface connection strength. The improvement in interface connection strength comes from the stress dispersion effect achieved under the condition of parallel covalent bonds, which disperses the extremely high stress on the polymer main chain on multiple weaker interactions, thereby achieving a significant improvement in overall connection strength.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of inorganic material surface treatment, and in particular to a method for enhancing inorganic material-polymer interface connection strength. Background Art

[0002] The bonding strength between inorganic and polymeric interfaces is an important basis for the utilization of many composite materials. For example, for the modification of the interface between gold and polymeric materials, the monolayer formed by self-assembly of thiols on the gold surface has been widely used to stabilize and functionalize the gold surface due to its stability, high efficiency and easy handling. Similarly, in the modification of the interface between silicon-based materials (silicon, silicon dioxide, silicon nitride, etc.) and polymers, the monolayer formed by self-assembly of silanization agents (silanization coupling) has become the most important means. Although such covalent bonding is generally considered to be stable, under swelling conditions, surface-induced polymer films can be easily detached from the gold or silicon surface, which is mainly attributed to the direct breakage of the gold-sulfur interaction and the promoted hydrolysis process of the silicon-oxygen bond. This instability of the inorganic material-polymer interface under stress conditions significantly limits the stability and application prospects of inorganic-polymer composites under stress and water conditions.

[0003] In addition to the field of material preparation, polymer fixation methods based on gold-sulfur interactions and silanization coupling are often widely used in single-molecule force chemistry / mechanical biology research, and the main research technology is single-molecule force spectroscopy based on atomic force microscopy. Single-molecule force spectroscopy, which has extremely high spatial (sub-nanometer) and force (pico-Newton) accuracy, is a powerful tool for measuring intramolecular or intermolecular interactions of natural and synthetic macromolecules. However, if the interface connection used in the experiment does not provide sufficient force stability (for example, the interface connection strength is weaker than the mechanical stability of the analyte), it is difficult to obtain structural information of the analyte from the force-stretch curve. For this reason, a long-term topic in the field of single-molecule force spectroscopy is to develop stable connection methods to expand the range of measurable forces. In fact, the weak gold-sulfur interaction (less than 0.6nN) limits the experimental range of single-molecule force spectroscopy on the surface of gold-coated substrates (the activation conditions of conventional force chemical reactions are usually higher than 1nN), and although the silicon-oxygen bond used in silanization coupling can provide relatively high mechanical strength (about 1.8nN), the easy hydrolysis of silicon-oxygen bonds under stress conditions makes it difficult for this coupling chemistry to provide continuous monitoring under high stress environments at the single-molecule level. The above defects have led to the failure of the universality of single-molecule force spectroscopy technology and its stability under extreme conditions to meet expectations. Summary of the invention

[0004] In view of this, the object of the present invention is to provide a method for enhancing the interface connection strength between inorganic materials and polymers. The present invention uses dendritic molecules and branched molecules to form a parallel covalent bond structure on the surface of the inorganic material, thereby improving the interface connection strength between the inorganic material and the polymer.

[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0006] The present invention provides a method for enhancing the inorganic material-polymer interface connection strength, comprising the following steps:

[0007] Functionalizing the inorganic material to obtain a functionalized inorganic material, wherein the functionalization is hydroxylation, carboxylation or epoxidation;

[0008] The functionalized inorganic material reacts with a compound to form a parallel covalent bond, the compound is a dendritic molecule or a branched molecule, and the reaction is an esterification reaction, an amidation reaction or an addition reaction.

[0009] Preferably, the dendritic molecule has a structure shown in Formula I:

[0010]

[0011] Preferably, the dendritic molecule is a PAMAM dendritic polymer with a CAS number of 153891-46-4.

[0012] Preferably, the inorganic material comprises gold, silicon, quartz or polydimethylsiloxane.

[0013] Preferably, when the inorganic material is gold, the hydroxylation comprises the following steps: immersing the gold in a solution of a compound containing both a hydroxyl group and a thiol group;

[0014] The reaction comprises the following steps: mixing the functionalized inorganic material with the dendritic molecule for esterification reaction, and mixing the obtained esterification product with trifluoroacetic acid to remove the CBZ protecting group of the amino group, wherein the CBZ protecting group has a structure shown in Formula II:

[0015]

[0016] In the formula II, * represents a connection site.

[0017] Preferably, when the inorganic material is gold, the carboxylation comprises the following steps: immersing the gold in a solution of a compound containing both a carboxyl group and a thiol group;

[0018] The reaction comprises the following steps: mixing the functionalized inorganic material with the dendritic molecule to perform an amidation reaction.

[0019] Preferably, the compound containing both a carboxyl group and a thiol group comprises mercaptoundecanoic acid, 6-mercaptohexanoic acid or 8-mercaptooctanoic acid.

[0020] Preferably, when the inorganic material is silicon, the hydroxylation comprises the following steps: immersing the silicon in a solution of 3-glycidyloxypropylmethyldiethoxysilane to perform a silylation reaction to obtain epoxidized silicon; performing an acid-catalyzed ring-opening reaction on the epoxidized silicon to obtain alcoholic hydroxyl-modified silicon;

[0021] The reaction comprises the following steps: mixing the alcoholic hydroxyl-modified silicon with a dendritic molecule for esterification reaction, and mixing the obtained esterification product with trifluoroacetic acid to remove the CBZ protecting group of the amino group, wherein the CBZ protecting group has a structure shown in Formula II:

[0022]

[0023] In the formula II, * represents a connection site.

[0024] Preferably, when the inorganic material is silicon or quartz, the carboxylation comprises the following steps: soaking the inorganic material in a solution of sodium salt of carboxyethylsilanol triol;

[0025] The reaction comprises the following steps: mixing the functionalized inorganic material with the dendritic molecule to perform an amidation reaction.

[0026] Preferably, when the inorganic material is polydimethylsiloxane, the epoxidation comprises the following steps: coating 3-glycidyloxypropylmethyldiethoxysilane on the surface of the polydimethylsiloxane for epoxidation reaction;

[0027] The reaction comprises the following steps: mixing the functionalized inorganic material with the dendritic molecule to perform an addition reaction.

[0028] The present invention provides a method for enhancing the interface connection strength between an inorganic material and a polymer, comprising the following steps: functionalizing an inorganic material to obtain a functionalized inorganic material, wherein the functionalization is hydroxylation, carboxylation or epoxidation; reacting the functionalized inorganic material with a compound to form a parallel covalent bond, wherein the compound is a dendritic molecule or a branch-like molecule, and the reaction is an esterification reaction, an amidation reaction or an addition reaction.

[0029] The present invention uses parallel covalent bonds to achieve inorganic material-polymer interface connection, which can improve the interface connection strength. The improvement in interface connection strength comes from the stress dispersion effect achieved under the condition of parallel covalent bonds, which disperses the extremely high stress on the polymer main chain on multiple weaker interactions, thereby achieving a significant improvement in the overall connection strength. Benefiting from the stress dispersion, the silicon-oxygen bonds that are sensitive to mechanical force can maintain a longer life under conditions of weaker stress, thereby achieving long-term and high-stress single-molecule force spectroscopy testing based on atomic force microscopy. Due to the improvement in interface connection strength, special chemical bonds on the interface can be selectively broken when the material is subjected to stress, thereby achieving patterning of chemical functional groups and preparing nanoribbons.

[0030] The data of the embodiments show that the silicon-polymer interface connection structure prepared by the method proposed in the present invention can achieve a single molecular chain subjected to a force of 1.8 nanonewtons and maintain an extremely long life of more than 30 seconds in a single molecule force spectroscopy test based on an atomic force microscope; the method proposed in the present invention can be used to perform PDMS nanoimprinting to prepare a strip structure with a resolution better than 300 nanometers. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 This is a schematic diagram of the gold surface treatment using dendron molecules in Example 1;

[0032] Figure 2 This is a schematic diagram of the gold surface treatment using dendrimers in Example 2;

[0033] Figure 3 This is a schematic diagram of the silicon surface treatment using dendron molecules in Example 3;

[0034] Figure 4 This is a schematic diagram of the surface treatment of silicon or quartz wafer using dendrimers in Example 4;

[0035] Figure 5 This is a schematic diagram of the surface treatment of PDMS nanostamp using dendrimers in Example 5;

[0036] Figure 6 is a typical force signal diagram in comparative example 1;

[0037] Figure 7 The typical force signal diagram and statistical data in Control Example 2;

[0038] Figure 8 Flow chart for chemical bond calibration of the surface of control example 3;

[0039] Fig. 9It is the fluorescence microscopy image of control example 3;

[0040] Fig.10 This is a typical force signal diagram of a gold-coated glass slide functionalized in Example 1 in Example 6;

[0041] Fig.11 This is a typical force signal diagram of a gold-coated glass slide functionalized in Example 2 in Example 6;

[0042] Fig.12 A bar graph is drawn for the fracture forces obtained for the modified gold-plated probes of Examples 1 and 2 and Control Example 1;

[0043] Fig.13 This is a surface treatment combined structure diagram of a large-sized gold-plated probe, a silicon nitride probe, a gold-plated substrate, and a silicon substrate in Example 6;

[0044] Fig.14 is a typical force curve of the optimized conditions in Example 6;

[0045] Fig.15 It is a statistical diagram of the breaking force under the optimized conditions in Example 6;

[0046] Fig.16 A is a typical force signal diagram in Example 7, and B is a normalized single molecule force spectrum data and a rupture force statistics diagram;

[0047] Fig.17 A is a schematic diagram of the reciprocating stretching experiment in Example 8, B is a typical force signal diagram, and C is a single cycle stretching force curve;

[0048] Fig.18 A is the force-stretch length curve of the force clamp experiment in Example 8, B is the force-time and stretch length-time curves of the dwell stage during the force clamp process, and C is the complete force-time curve during the force clamp process;

[0049] Fig.19 This is a flow chart of the chemical bond calibration of the surface in Example 9;

[0050] Fig. 20 These are the fluorescence microscopy and atomic force microscopy images in Example 9. DETAILED DESCRIPTION

[0051] The present invention provides a method for enhancing the inorganic material-polymer interface connection strength, comprising the following steps:

[0052] Functionalizing the inorganic material to obtain a functionalized inorganic material, wherein the functionalization is hydroxylation, carboxylation or epoxidation;

[0053] The functionalized inorganic material reacts with a compound to form a parallel covalent bond, the compound is a dendritic molecule or a branched molecule, and the reaction is an esterification reaction, an amidation reaction or an addition reaction.

[0054] In the present invention, unless otherwise specified, the raw materials used are all commercially available products in the art.

[0055] In the present invention, the dendritic molecule preferably has a structure shown in Formula I:

[0056]

[0057] In the present invention, the CAS number of the dendritic molecule is 1076689-77-4, preferably purchased from NSB POSTECH Inc., and the dendritic molecule undergoes esterification reaction between the nine carboxyl groups at the molecular ends and the hydroxyl groups on the surface of the inorganic material to form nine parallel ester bonds.

[0058] In the present invention, the dendritic molecule is preferably a PAMAM dendritic polymer with a CAS number of 153891-46-4.

[0059] In the present invention, the inorganic material preferably includes gold, silicon, quartz or polydimethylsiloxane (PDMS).

[0060] In the present invention, when the inorganic material is gold, the hydroxylation comprises the following steps: immersing the gold in a solution of a compound containing both a hydroxyl group and a thiol group;

[0061] The reaction comprises the following steps: mixing the functionalized inorganic material with the dendritic molecule for esterification reaction, and mixing the obtained esterification product with trifluoroacetic acid to remove the CBZ protecting group of the amino group, wherein the CBZ protecting group has a structure shown in Formula II:

[0062]

[0063] In the formula II, * represents a connection site.

[0064] In the present invention, the gold is preferably used in the form of a gold-coated slide glass.

[0065] In the present invention, the gold-plated glass slide is preferably pretreated before use, and the pretreatment preferably includes ultrasonic washing, UV-ozone washing, water washing and drying in sequence. In the present invention, the ultrasonic washing is preferably ultrasonicated in chloroform, ethanol and deionized water for 10 minutes in sequence to remove potential pollutants. In the present invention, the UV-ozone washing is preferably carried out in a UV-ozone cleaning instrument, the temperature is preferably 100°C, and the time is preferably 30 minutes. The role of the UV-ozone washing is to further clean and oxidize. In the present invention, the drying is preferably oven drying. The present invention has no special restrictions on the specific parameters of the drying, as long as the moisture can be completely removed.

[0066] In the present invention, the compound containing both hydroxyl and thiol preferably includes 6-mercapto-1-hexanol, 2-mercaptoethanol, or 3-mercapto-1-propanol. The present invention utilizes the gold-thiol interaction to allow the compound containing both hydroxyl and thiol to self-assemble into a monomolecular film on the gold surface, thereby modifying the gold surface into a hydroxyl surface.

[0067] In the present invention, the concentration of the solution of the compound containing both a hydroxyl group and a thiol group is preferably 1 mM, and the solvent of the solution of the compound containing both a hydroxyl group and a thiol group is preferably ethanol.

[0068] In the present invention, the soaking time is preferably 24 hours.

[0069] After the hydroxylation is completed, it is preferred that the obtained hydroxylation product is sequentially washed with ethanol and dried to obtain the functionalized inorganic material.

[0070] In the present invention, the drying is preferably performed at room temperature.

[0071] In the present invention, the dendritic molecules are preferably soaked in the functionalized inorganic material in the form of a dendritic molecule solution.

[0072] In the present invention, the concentration of the dendritic molecule solution is preferably 1 mM.

[0073] In the present invention, the esterification reaction is preferably carried out in a DCM-DMF mixed solution containing DCC and DMAP, and the volume ratio of DCM to DMF in the DCM-DMF mixed solution is preferably 1 to 3: 1. In the present invention, the concentration of DCC in the DCM-DMF mixed solution is preferably 18 mM, the concentration of DMAP is preferably 0.9 mM, and the DCC and DMAP are catalysts.

[0074] In the present invention, the temperature of the esterification reaction is preferably room temperature, i.e., no additional heating or cooling is required, and the time is preferably 24 hours. The process of the esterification reaction is to prepare parallel covalent bonds (ester bonds) in order to disperse the larger mechanical force on the molecular skeleton (the position of the anthracene group is the position of the molecular skeleton) on these 9 ester bonds in the final connection structure, so as to avoid the desorption behavior of the target molecule-gold caused by the instability of the interface connection.

[0075] After the esterification reaction is completed, the present invention preferably further comprises washing with DCM and methanol in sequence and then drying with nitrogen.

[0076] In the present invention, the esterification product is preferably immersed in a trifluoroacetic acid (TFA) solution (1 M) in DCM to remove the protecting group, exposing the amino group for connecting the polymer molecule.

[0077] In the present invention, after the removal of the protecting group is completed, the obtained product is preferably washed with DCM and methanol in sequence and kept ready for connection with the target polymer.

[0078] In the present invention, the target polymer is preferably a polymer containing a carboxyl group, and the polymer containing a carboxyl group is preferably carboxymethyl starch.

[0079] In the present invention, when the inorganic material is gold, the carboxylation comprises the following steps: immersing the gold in a solution of a compound containing both a carboxyl group and a thiol group;

[0080] The reaction comprises the following steps: mixing the functionalized inorganic material with the dendritic molecule to perform an amidation reaction.

[0081] In the present invention, the gold is preferably pretreated, and the pretreatment is preferably consistent with the above scheme, which will not be described in detail here.

[0082] In the present invention, the compound containing both carboxyl and thiol includes mercaptoundecanoic acid, 6-mercaptohexanoic acid or 8-mercaptooctanoic acid, and the carboxylated gold surface is prepared by utilizing the gold-thiol interaction.

[0083] In the present invention, the concentration of the solution of the compound containing both a carboxyl group and a thiol group is preferably 1 mM.

[0084] In the present invention, the soaking time is preferably 24 hours.

[0085] After the carboxylation is completed, the method preferably further comprises washing the obtained carboxylation product with ethanol and drying in sequence to obtain the functionalized inorganic material.

[0086] In the present invention, the drying is preferably performed at room temperature.

[0087] In the present invention, the dendrimer molecules are preferably used to soak the functionalized inorganic material in the form of a dendrimer molecule solution.

[0088] In the present invention, the concentration of the dendrimer solution is preferably 5 mM.

[0089] In the present invention, the amidation reaction is preferably carried out in a PBS buffer, wherein the PBS buffer preferably contains 4 mg / mL of EDC and 4 mg / mL of NHS, and the EDC and NHS serve as catalysts.

[0090] In the present invention, the temperature of the amidation reaction is preferably room temperature, i.e., no additional heating or cooling is required, and the time is preferably 24 hours. During the amidation reaction, the amino groups on the outer sides of the dendritic molecules and the carboxylation products form parallel amide bonds through the amidation reaction, and the number of amide bonds formed between each dendritic molecule and the carboxylation product is 16.

[0091] After the amidation reaction is completed, the product is preferably washed with deionized water and methanol in sequence and then dried with nitrogen for standby use until the target polymer is connected.

[0092] In the present invention, the target polymer is preferably a polymer containing a carboxyl group, and the polymer containing a carboxyl group is preferably carboxymethyl starch.

[0093] In the present invention, when the inorganic material is silicon, the hydroxylation comprises the following steps: immersing the silicon in a solution of 3-glycidyloxypropylmethyldiethoxysilane to perform a silylation reaction to obtain epoxidized silicon; performing an acid-catalyzed ring-opening reaction on the epoxidized silicon to obtain alcoholic hydroxyl-modified silicon;

[0094] The reaction comprises the following steps: mixing the alcoholic hydroxyl-modified silicon with a dendritic molecule for esterification reaction, and mixing the obtained esterification product with trifluoroacetic acid to remove the CBZ protecting group of the amino group, wherein the CBZ protecting group has a structure shown in Formula II:

[0095]

[0096] In the formula II, * represents a connection site.

[0097] In the present invention, the silicon is preferably used in the form of a silicon wafer.

[0098] In the present invention, the silicon wafer is preferably pretreated before use, and the pretreatment preferably includes ultrasonic cleaning, ultraviolet-ozone cleaning, water washing and drying in sequence. In the present invention, the ultrasonic cleaning is preferably ultrasonicated in chloroform, ethanol and deionized water for 10 minutes in sequence to remove potential pollutants. In the present invention, the ultraviolet-ozone cleaning is preferably carried out in an ultraviolet-ozone cleaning apparatus, the temperature is preferably 100°C, and the time is preferably 30 minutes. The role of the ultraviolet-ozone cleaning is to further clean and oxidize to produce silicon hydroxyl groups for silanization reaction. In the present invention, the drying is preferably oven drying. The present invention has no special restrictions on the specific parameters of the drying, as long as the moisture can be completely removed.

[0099] In the present invention, the solvent of the solution of 3-glycidyloxypropylmethyldiethoxysilane is preferably anhydrous xylene, and the volume concentration of the solution of 3-glycidyloxypropylmethyldiethoxysilane is preferably 1%.

[0100] In the present invention, the soaking time is preferably 24 hours.

[0101] In the present invention, the temperature of the silanization reaction is preferably room temperature, that is, no additional heating or cooling is required, and the time is preferably 24 hours.

[0102] In the present invention, the obtained soaking product is preferably rinsed with xylene, a xylene-methanol mixture and methanol in sequence, and heated at 110° C. for 30 minutes, and naturally cooled to room temperature to obtain epoxidized silicon.

[0103] In the present invention, the volume ratio of xylene to methanol in the xylene-methanol mixture is preferably 1:1.

[0104] The present invention preferably immerses the epoxidized silicon in an ethylene glycol solution of sulfuric acid to carry out the acid-catalyzed ring-opening reaction, and completes the hydroxylation of the silicon wafer surface through the acid-catalyzed ring-opening of the epoxy.

[0105] In the present invention, the volume concentration of sulfuric acid in the ethylene glycol solution of sulfuric acid is preferably 0.5%, the temperature is preferably 90° C.; and the soaking time is preferably 8 hours.

[0106] In the present invention, the GPDES (3-glycidyloxypropylmethyldiethoxysilane) molecule contains an epoxy group, and the two silicon-oxygen-carbon bonds in the GPDES molecule undergo a silanization reaction with the silanol groups on the silicon surface to form two silicon-oxygen-silicon bonds, thereby introducing the epoxy group into the silicon wafer surface, followed by ring opening under acid catalysis to finally prepare epoxidized silicon.

[0107] After the silanization is completed, the hydroxylated silicon wafer is preferably washed with DCM and methanol in sequence and then dried at room temperature.

[0108] In the present invention, the dendritic molecules are preferably soaked in the functionalized inorganic material in the form of a dendritic molecule solution.

[0109] In the present invention, the concentration of the dendritic molecule solution is preferably 1 mM.

[0110] In the present invention, the esterification reaction is preferably carried out in a DCM-DMF mixed solution containing DCC and DMAP, and the volume ratio of DCM to DMF in the DCM-DMF mixed solution is preferably 1 to 3: 1. In the present invention, the concentration of DCC in the DCM-DMF mixed solution is preferably 18 mM, the concentration of DMAP is preferably 0.9 mM, and the DCC and DMAP are catalysts.

[0111] In the present invention, the temperature of the esterification reaction is preferably room temperature, that is, no additional heating or cooling is required, and the time is preferably 24 hours. The process of the esterification reaction is to prepare parallel covalent bonds (ester bonds) in order to disperse the larger mechanical force on the molecular skeleton (the position of the anthracene group is the position of the molecular skeleton) on these 9 ester bonds in the final connection structure, so as to avoid the desorption behavior of the target molecule-silicon caused by the instability of the interface connection.

[0112] After the esterification reaction is completed, the present invention preferably further comprises washing with DCM and methanol in sequence and then drying with nitrogen.

[0113] In the present invention, the esterification product is preferably immersed in a trifluoroacetic acid (TFA) solution (1 M) in DCM to remove the protecting group, exposing the amino group for connecting the polymer molecule.

[0114] In the present invention, after the removal of the protecting group is completed, the obtained product is preferably washed with DCM and methanol in sequence and kept ready for connection with the target polymer.

[0115] In the present invention, the target polymer is preferably a polymer containing a carboxyl group, and the polymer containing a carboxyl group is preferably carboxymethyl starch.

[0116] In the present invention, when the inorganic material is silicon or quartz, the carboxylation comprises the following steps: soaking the inorganic material in a solution of sodium salt of carboxyethylsilanol triol;

[0117] The reaction comprises the following steps: mixing the functionalized inorganic material with the dendritic molecule to perform an amidation reaction.

[0118] In the present invention, the silicon and quartz are preferably pretreated, and the pretreatment is preferably consistent with the above-mentioned solution for treating silicon, which will not be repeated here.

[0119] In the present invention, the solvent of the solution of sodium salt of carboxyethylsilicontriol is preferably water, the mass fraction of sodium salt of carboxyethylsilicontriol in the solution of sodium salt of carboxyethylsilicontriol is preferably 0.5%, the pH value of the solution of sodium salt of carboxyethylsilicontriol is preferably 4-6, and the present invention preferably uses hydrochloric acid to adjust the pH value.

[0120] In the present invention, the soaking time is preferably 24 hours.

[0121] After the soaking is completed, the present invention preferably washes the solid with ultrapure water three times and then heats it to carboxylate the surfaces of the silicon wafer and the quartz wafer.

[0122] In the present invention, the heating temperature is preferably 110° C., the heating time is preferably 30 min, and the heating is preferably performed in an oven.

[0123] In the present invention, the dendrimer molecules are preferably used to soak the functionalized inorganic material in the form of a dendrimer molecule solution.

[0124] In the present invention, the concentration of the dendrimer solution is preferably 5 mM.

[0125] In the present invention, the amidation reaction is preferably carried out in a PBS buffer, wherein the PBS buffer preferably contains 4 mg / mL of EDC and 4 mg / mL of NHS, and the EDC and NHS serve as catalysts.

[0126] In the present invention, the temperature of the amidation reaction is preferably room temperature, i.e., no additional heating or cooling is required, and the time is preferably 24 hours. During the amidation reaction, the amino groups on the outer sides of the dendritic molecules and the carboxylation products form parallel amide bonds through the amidation reaction, and the number of amide bonds formed between each dendritic molecule and the carboxylation product is 16.

[0127] After the amidation reaction is completed, the product is preferably washed with deionized water and methanol in sequence and then dried with nitrogen for standby use until the target polymer is connected.

[0128] In the present invention, the target polymer is preferably a polymer containing a carboxyl group, and the polymer containing a carboxyl group is preferably carboxymethyl starch.

[0129] In the present invention, when the inorganic material is polydimethylsiloxane, the epoxidation comprises the following steps: coating 3-glycidyloxypropylmethyldiethoxysilane on the surface of the polydimethylsiloxane for epoxidation reaction;

[0130] The reaction comprises the following steps: mixing the functionalized inorganic material with the dendritic molecule to perform an addition reaction.

[0131] The present invention has no particular limitation on the specific source of the polydimethylsiloxane, and it can be prepared by a preparation method well known to those skilled in the art. In the embodiment of the present invention, a PDMS nanostamp is used, and the specific preparation method is as follows:

[0132] Mix the Sylgard 184 kit and the curing agent in a ratio of 10:1 (w / w) and stir thoroughly;

[0133] The mixed solution was treated in vacuum for 30 minutes to eliminate bubbles generated during stirring;

[0134] The solution is then poured onto the template (DVD disc) and vacuumed again to fill in all the gaps in the strip;

[0135] The mixture was cured in an oven at 80 °C for 4 h and then demolded to obtain a cured PDMS nanostamp.

[0136] The present invention preferably sequentially rinses the PDMS nanostamp with deionized water, treats it with UV-ozone, and dries it. The UV-ozone treatment is preferably performed for 30 minutes to generate silanol groups for fixing GPDES. The drying is preferably performed in a dryer containing P2O5 for 10 minutes.

[0137] In the present invention, the epoxidation reaction preferably comprises the following steps:

[0138] The polydimethylsiloxane and GPDES are sealed at room temperature to form a self-assembled monolayer on the surface of the PDMS nanostamp;

[0139] The sealed product was washed with methanol and baked at 115° C. for 15 min to covalently bond the GPDES, thereby obtaining an epoxidized PDMS nanostamp.

[0140] In the present invention, the sealing time is preferably 6 to 12 hours.

[0141] In the present invention, the dendritic molecules are preferably coated on the functionalized inorganic material in the form of spin coating of a dendritic molecule ethanol solution, the concentration of the dendritic molecule ethanol solution is preferably 0.5 wt %, the spin coating speed is preferably 2500 rpm, and the spin coating time is preferably 60 s.

[0142] In the present invention, the temperature of the addition reaction is preferably 115° C., and the time is preferably 15 min, so that the epoxy group forms a carbon-nitrogen bond with the dendritic molecule. During the addition reaction, the amino group on the outside of the dendritic molecule and the epoxidation product form parallel carbon-nitrogen bonds through addition reaction, and the number is 16 carbon-nitrogen bonds formed by each dendritic molecule and the carboxylation product. The reaction mechanism is the addition of primary amine and epoxy group.

[0143] After the addition reaction is completed, the solid product is preferably subjected to ultrasonic treatment in ethanol for 3 times, each time for 5 minutes, to remove all non-covalently adsorbed dendritic molecules, and then dried with nitrogen for standby use until the target molecule is connected.

[0144] In the present invention, the target molecule is preferably a molecule containing a carboxyl group, and the molecule containing a carboxyl group is preferably succinic acid.

[0145] Terminology explanation:

[0146] DMAP: 4-Dimethylaminopyridine;

[0147] DCC: Dicyclohexylcarbodiimide;

[0148] DCM: Dichloromethane;

[0149] DMF: N,N-Dimethylformamide;

[0150] TFA: Trifluoroacetic acid;

[0151] EDC:1-(3-Dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride, 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide;

[0152] NHS: N-Hydroxy succinimide

[0153] PDMS: Polydimethylsiloxane

[0154] CES:Carboxyethylsilanetriol sodium salt

[0155] GPDES: (3-Glycidoxypropyl)methyldiethoxysilane

[0156] APTMS: (3-Aminopropyl)trimethoxysilane

[0157] PBS buffer: phosphate buffered saline, phosphate buffered saline

[0158] PS-PMAA: poly(styrene–co–methacrylic acid), styrene-methacrylic acid copolymer Sulfo-NHS: N-Hydroxysulfosuccinimide sodium salt, N-hydroxysulfosuccinimide.

[0159] In order to further illustrate the present invention, the method for enhancing the inorganic material-polymer interface connection strength provided by the present invention is described in detail below with reference to examples, but they should not be construed as limiting the protection scope of the present invention.

[0160] EDC, NHS, DCC, DMAP, APTMS, GPDES and TFA were purchased from SigmaAldrich. Anhydrous DCM, anhydrous DMF, anhydrous xylene, CES aqueous solution, 6-mercapto-1-hexanol, and 11-mercaptoundecanoic acid were purchased from J&K Scientific. Dendrimers (PAMAM, CYD-130A) were purchased from Weihai Chenyuan Molecular New Materials Co., Ltd. Dendrimers were purchased from NSB Postech, Inc. Sylgard 184 kit was purchased from Dow Corning.

[0161] Example 1: Using dendrons to treat the surface of gold. The principle is as follows: Figure 1 shown.

[0162] The gold-coated slides were sonicated in chloroform, ethanol, and deionized water for 10 min, respectively;

[0163] The gold-coated slides were transferred to a UV-ozone cleaner and further cleaned and oxidized at 100 °C for 30 min;

[0164] The oxidized gold-coated slides were rinsed with deionized water and dried in an oven;

[0165] The cleaned gold-coated slides were immersed in an ethanol solution of 1 mM 6-mercapto-1-hexanol for 24 h;

[0166] Rinse the gold-coated slides thoroughly with ethanol and dry at room temperature;

[0167] The gold-coated glass slide was immersed in a DCM-DMF (1:1 volume ratio) solution containing 0.9 mM DMAP, 1 mM dendrimer (CAS: 1076689-77-4), and 18 mM DCC for 24 hours;

[0168] The gold-coated slides were rinsed with DCM and methanol in sequence and blown dry with nitrogen gas;

[0169] The gold-coated glass slide was immersed in a TFA solution in DCM (1 M) to remove the protecting groups and expose the amino groups for connecting polymer molecules;

[0170] Rinse the gold-coated slide with DCM and methanol sequentially and set aside until the target polymer is attached

[0171] Example 2: Using dendrimers to treat the surface of gold. The principle is as follows: Figure 2 shown.

[0172] The gold-coated slides were sonicated in chloroform, ethanol, and deionized water for 10 min, respectively;

[0173] The gold-coated slides were transferred to a UV-ozone cleaner and further cleaned and oxidized at 100 °C for 30 min;

[0174] The oxidized gold-coated slides were rinsed with deionized water and dried in an oven;

[0175] The cleaned gold-coated slide was immersed in a 1 mM 11-mercaptoundecanoic acid (mercaptoundecanoic acid) ethanol solution for 24 h;

[0176] Rinse the gold-coated slides thoroughly with ethanol and dry at room temperature;

[0177] The gold-coated glass slide modified with the carboxyl group was immersed in a PBS buffer containing 5 mM dendrimer (CAS: 153891-46-4), 4 mg / mL EDC and 4 mg / mL NHS, and incubated at room temperature for 24 hours;

[0178] The gold-coated glass slide was rinsed with deionized water and methanol in sequence, dried with nitrogen gas, and kept ready for connection with the target polymer.

[0179] Example 3: Using dendrons to treat silicon surface. Figure 3 shown.

[0180] The cut silicon wafers were ultrasonicated in chloroform, ethanol and deionized water for 10 min in sequence;

[0181] The silicon wafer was transferred to a UV-ozone cleaner and further cleaned and oxidized at 100 °C for 30 min;

[0182] The oxidized silicon wafer was rinsed with deionized water and dried in an oven;

[0183] The cleaned silicon wafer was immersed in GPDES anhydrous xylene solution (1%, volume ratio) for 24 h;

[0184] The silicon wafer was rinsed with xylene, xylene-methanol (1 / 1 volume ratio) and methanol in sequence, and heated at 110° C. for 30 minutes;

[0185] After cooling to room temperature, the silicon wafer was immersed in an ethylene glycol solution containing 0.5% (volume ratio) sulfuric acid at 90° C. for 8 hours to complete the hydroxylation of the silicon wafer surface through the acid-catalyzed ring opening of the epoxy;

[0186] The hydroxylated silicon wafer is washed with ethanol and methanol in sequence and dried at room temperature;

[0187] The silicon wafer was immersed in a DCM-DMF (1:1 volume ratio) solution containing 0.9 mM DMAP, 1 mM dendron molecule (CAS: 1076689-77-4), and 18 mM DCC for 24 hours;

[0188] The silicon wafer was rinsed with DCM and methanol in sequence and dried with nitrogen;

[0189] The silicon wafer was immersed in a TFA solution in DCM (1 M) to remove the protecting groups and expose the amino groups for connecting polymer molecules;

[0190] The silicon wafer was rinsed with DCM and methanol in sequence and set aside for attachment to the target polymer.

[0191] Example 4: Using dendrimers to treat the surface of silicon or quartz wafers. The principle is as follows: Figure 4 shown.

[0192] The cut silicon wafer or quartz wafer was ultrasonicated in chloroform, ethanol and deionized water for 10 minutes in turn;

[0193] Transfer the silicon wafer or quartz wafer to a UV-ozone cleaner and further clean and oxidize at 100°C for 30 minutes;

[0194] The oxidized silicon wafer or quartz wafer is rinsed with deionized water and dried in an oven;

[0195] Soak the cleaned silicon wafer or quartz wafer in a CES aqueous solution (0.5% mass fraction, pH adjusted to 4 with hydrochloric acid) for 24 hours;

[0196] The silicon wafer or quartz wafer is washed three times with ultrapure water and transferred to a 110° C. oven for heating for 30 minutes to carboxylate the surface of the silicon wafer, quartz wafer or PDMS;

[0197] The carboxylated silicon or quartz wafer was cooled to room temperature and immersed in PBS buffer containing 5 mM dendrimer (CAS: 153891-46-4), 4 mg / mL EDC, and 4 mg / mL NHS, and incubated at room temperature for 24 h;

[0198] The silicon wafer or quartz wafer is rinsed with deionized water and methanol in turn, blown dry with nitrogen gas, and set aside for connection with the target polymer.

[0199] Example 5: Using dendrimers to treat the surface of PDMS (polydimethylsiloxane) nanostamps. The principle is as follows: Figure 5 shown.

[0200] The Sylgard 184 kit and the curing agent were mixed at a ratio of 10:1 (w / w) and stirred thoroughly to prepare a PDMS nanostamp;

[0201] The mixed solution was treated in vacuum for 30 minutes to eliminate bubbles generated during stirring;

[0202] The solution is then poured onto the template (DVD disc) and vacuumed again to fill in all the gaps in the strip;

[0203] The mixture was cured in an oven at 80 °C for 4 h and then demolded to obtain a cured PDMS nanostamp;

[0204] The PDMS nanostamp was rinsed with deionized water and treated with UV-ozone for 30 min to generate silanol groups for GPDES fixation;

[0205] The PDMS nanostamp was placed in a desiccator containing P2O5 for 10 minutes, and then 40 μl of GPDES was added, and the desiccator was sealed overnight at room temperature to form a self-assembled monolayer on the surface of the PDMS nanostamp;

[0206] After being rinsed with methanol three times, the nanostamps were baked at 115 °C for 15 min to covalently bond GPDES, i.e., epoxidized PDMS;

[0207] The cooled PDMS nanostamp was spin-coated with a dendrimer (CAS: 153891-46-4) solution (0.5%, ethanol as solvent) and baked at 115°C for 15 minutes to form covalent bonds between the epoxy groups and the dendrimer;

[0208] The PDMS nanostamp was sonicated in ethanol three times for 5 min each to remove all non-covalently adsorbed dendrimers;

[0209] Finally, the PDMS nanostamp modified with the dendrimers was dried with nitrogen gas for subsequent use.

[0210] Comparative Example 1: Connection Strength of Non-Parallel Covalent Bonds on the Surface of Gold-Coated Glass Slide (Traditional Experimental Method)

[0211] The gold-coated slides were sonicated in chloroform, ethanol, and deionized water for 10 min, respectively;

[0212] The gold-coated slide and gold-coated probe were transferred to a UV-ozone cleaner and further cleaned and oxidized at 100 °C for 30 min;

[0213] The oxidized gold-coated slides and gold-coated probes were rinsed with deionized water and dried in an oven;

[0214] The cleaned gold-coated slide and gold-coated probe were immersed in an ethanol solution of cysteamine with a concentration of 1 mM for 24 h;

[0215] Rinse the gold-coated slide and gold-coated probe thoroughly with ethanol and dry at room temperature;

[0216] PBS buffer containing carboxymethyl starch (20 mg / mL), EDC (20 mg / mL) and NHS (20 mg / mL) was added dropwise to the functionalized gold-coated glass slide surface and allowed to stand for 30 minutes to allow the carboxymethyl starch to form a stable covalent connection with the gold-coated glass slide surface;

[0217] The gold-coated glass slides attached with carboxymethyl starch were rinsed with PBS buffer and mounted in an atomic force microscope for single-molecule force spectroscopy experiments using the functionalized gold-coated probes described above. All single-molecule force spectroscopy experiments were performed in PBS buffer;

[0218] In the single-molecule force spectroscopy experiment, the spring constant of each cantilever beam was calibrated in a submerged liquid (PBS buffer) environment using the thermal noise method, and the obtained spring constant was 0.02 to 0.12 N / m;

[0219] In each single-molecule stretching process, the gold-plated probe of the atomic force microscope is in contact with the gold-plated glass slide connected with carboxymethyl starch. After the atomic force microscope probe and the carboxymethyl starch form a covalent bond, the tip of the gold-plated probe is controlled to retract from the gold-plated glass slide. During the retraction process, the molecular bridge formed between the gold-plated probe and the gold-plated glass slide can be stretched until the weakest part breaks. The stretching speed is 1.0 μm / s. The typical force signal obtained in the experiment is as follows: Figure 6 According to statistics, the breaking force is 0.5±0.1nN.

[0220] Comparative Example 2: Connection Strength of Non-Parallel Covalent Bonds on Silicon Wafer Surface (Traditional Experimental Method)

[0221] The cut silicon wafers were ultrasonicated in chloroform, ethanol and deionized water for 10 min in sequence;

[0222] The silicon wafer and silicon nitride probe were transferred to a UV-ozone cleaner and further cleaned and oxidized at 100 °C for 30 min;

[0223] The oxidized silicon wafer and silicon nitride probe were rinsed with deionized water and dried in an oven;

[0224] The cleaned silicon wafer and silicon nitride probe were immersed in an APTMS anhydrous xylene solution (1% by volume) for 2 hours;

[0225] The silicon wafer and silicon nitride probe were washed with xylene, xylene-methanol (1 / 1 volume ratio) and methanol in sequence, and then heated in an oven at 110° C. for 30 minutes to amino-dip the surfaces of the silicon wafer and silicon nitride probe;

[0226] The aminated silicon wafer was cooled to room temperature, and PBS buffer containing carboxymethyl starch (20 mg / mL), EDC (20 mg / mL) and NHS (20 mg / mL) was added dropwise to the functionalized silicon wafer surface and allowed to stand for 30 minutes to allow the carboxymethyl starch to form a stable covalent connection with the silicon wafer surface;

[0227] The silicon wafer with carboxymethyl starch attached was rinsed with PBS buffer and mounted in an atomic force microscope for single-molecule force spectroscopy experiments using the functionalized silicon nitride probe described above. All single-molecule force spectroscopy experiments were performed in PBS buffer;

[0228] In the single-molecule force spectroscopy experiment, the spring constant of each cantilever beam was calibrated in a submerged liquid (PBS buffer) environment using the thermal noise method, and the obtained spring constant was 0.02 to 0.12 N / m;

[0229] In each single-molecule stretching process, the atomic force microscope silicon nitride probe contacts the silicon wafer connected with carboxymethyl starch. After the atomic force microscope silicon nitride probe forms a covalent bond with the carboxymethyl starch, the silicon nitride probe tip is controlled to retract from the silicon wafer. During the retraction process, the molecular bridge formed between the silicon nitride probe and the silicon wafer can be stretched until the weakest part breaks. The stretching speed is 1.0 μm / s. The typical force signal diagram and statistical data obtained in the experiment are shown in Figure 2. Figure 7 According to statistics, the breaking force is 1.8±0.4nN.

[0230] Control Example 3 Patterned Mechanochemical Initiation on Quartz Slice Surface (Control Test)

[0231] A PBS buffer solution containing succinic acid (40 mg / mL), EDC (200 mg / mL) and Sulfo-NHS (200 mg / mL) was added dropwise to the surface of the quartz plate functionalized in Example 4, and allowed to stand for 30 minutes to allow the succinic acid to form a stable covalent connection with the surface of the quartz plate;

[0232] The epoxidized PDMS nanostamp prepared in Example 5 was pressed onto the surface of the quartz plate modified with succinic acid, and a pressure of 20 N was applied for 30 minutes;

[0233] The PDMS nanostamp was then vertically peeled off from the surface of the quartz slide;

[0234] The surface chemical bonds of the PDMS nanostamp and quartz sheet after peeling off were calibrated using aminofluorescein and carboxyl fluorescent microspheres, respectively, and finally the surface state was determined by fluorescence microscopy. The process is as follows: Figure 8 The results are shown in Fig. 9 , neither the PDMS nor the quartz sheet in the control group exhibited a clear fluorescent stripe structure, proving that parallel covalent bonds are the key factor in achieving mechanochemical reaction patterning in Example 4.

[0235] Example 6: Bonding strength of a single carboxymethyl starch molecule on a gold-coated glass slide and a silicon wafer

[0236] PBS buffer containing carboxymethyl starch (20 mg / mL), EDC (20 mg / mL) and NHS (20 mg / mL) was added dropwise to the surface of the gold-coated glass slide functionalized in Example 1, and allowed to stand for 30 minutes to allow the carboxymethyl starch to form a stable covalent bond with the surface of the gold-coated glass slide;

[0237] The gold-coated glass slide connected with carboxymethyl starch was rinsed with PBS buffer and mounted in an atomic force microscope for single-molecule force spectroscopy experiments. The gold-coated probe of the atomic force microscope was also functionalized using Scheme 1. All single-molecule force spectroscopy experiments were performed in PBS buffer;

[0238] In the single-molecule force spectroscopy experiment, the spring constant of each cantilever beam was calibrated in a submerged liquid (PBS buffer) environment using the thermal noise method, and the obtained spring constant was 0.02 to 0.12 N / m;

[0239] In each single-molecule stretching process, the gold-plated probe of the atomic force microscope is in contact with the gold-plated glass slide connected with carboxymethyl starch. After the atomic force microscope probe and the carboxymethyl starch form a covalent bond, the tip of the gold-plated probe is controlled to retract from the gold-plated glass slide. During the retraction process, the molecular bridge formed between the gold-plated probe and the gold-plated glass slide can be stretched until the weakest part breaks. The stretching speed is 1.0 μm / s. The typical force signal obtained in the experiment is as follows: Fig.10 According to statistics, the breaking force is 1.7±0.2nN. Compared with the control example 1, the connection strength is improved by 240%.

[0240] Similarly, the gold-coated glass slide functionalized in Example 2 was used. Its typical force curve is shown in Fig.11 As shown, according to statistics, the breaking force is 1.8±0.2nN, and the connection strength is improved by 260% compared with the control example 1.

[0241] For comparison, the fracture forces obtained by the modified gold-plated probes of Examples 1 and 2 and Control Example 1 were plotted in a bar graph, as shown in FIG. Fig.12 , proving that the experimental scheme using parallel covalent bonds can significantly improve the interface connection strength between the gold surface and the polymer. Among them, the gray line is the control example 1, the green line is the embodiment 1, and the red line is the embodiment 2.

[0242] Since the modification conditions of the AFM probe side in single-molecule force spectroscopy experiments are the same as those of the gold-coated glass slide or silicon wafer side, the properties of the probe may also affect the test results.

[0243] To optimize the conditions, the standard gold-plated probe was replaced with a large-size gold-plated probe (the tip curvature radius was increased from 25 nm to 60 nm), and the experimental conditions were arranged to test the best conditions, see Fig.13 , where (1) Example 2 is used as the interface modification condition for a standard gold-plated probe and a standard gold-plated glass slide; (2) Example 2 is used as the interface modification condition for a large-size gold-plated probe and a standard gold-plated glass slide; (3) Example 4 is used for a silicon nitride probe and Example 2 is used as the interface modification condition for a standard gold-plated glass slide; (4) Example 4 is used for a silicon nitride probe and Example 2 is used as the interface modification condition for an ultra-flat gold-plated glass slide; (5) Example 4 is used for a silicon nitride probe and a silicon wafer; (6) Example 3 is used for a silicon nitride probe and a silicon wafer. Typical force curves are shown as follows Fig.14 , where the fracture force range of the optimized conditions is marked with a light red area, and the fracture force statistics of all optimized conditions are shown in Fig.15 The experimental results show that the parallel covalent bond scheme can increase the connection strength of the polymer-gold interface by 350% (Comparison between (2-4) in Example 1 and Control Example 1), and can increase the connection strength of the polymer-silicon interface by 33% (Comparison between (5-6) in Example 1 and Control Example 2). This proves that the parallel covalent bond scheme is universal and effective for improving the connection strength of the polymer-inorganic material interface.

[0244] Example 7: Connection strength of a single PS-PMAA molecule on a silicon wafer surface

[0245] PS-PMAA (10 mg / mL), EDC (5 mg / mL) and NHS (3 mg / mL) dissolved in N,N-dimethylacetamide were added dropwise to the silicon wafer surface functionalized in Example 4 and allowed to stand for 30 minutes to allow PS-PMAA to form a stable covalent connection with the silicon wafer surface;

[0246] The silicon wafer connected with PS-PMAA was rinsed with N,N-dimethylacetamide and mounted in an atomic force microscope for single-molecule force spectroscopy experiments. The atomic force microscope probe used was a silicon nitride probe functionalized in Example 4.

[0247] In the single-molecule force spectroscopy experiment, the spring constant of each cantilever beam was calibrated in a liquid (N, N-dimethylacetamide) environment using the thermal noise method, and the obtained spring constant was 0.02-0.12N / m. All single-molecule force spectroscopy experiments were performed in N, N-dimethylacetamide.

[0248] In each single-molecule stretching process, the atomic force microscope silicon nitride probe contacts the silicon wafer connected with PS-PMAA. After the atomic force microscope silicon nitride probe forms a covalent bond with PS-PMAA, the silicon nitride probe tip is controlled to retract from the silicon wafer. During the retraction process, the molecular bridge formed between the silicon nitride probe and the silicon wafer can be stretched until the weakest part breaks. The stretching speed is 1.0 μm / s.

[0249] Typical force signals obtained from the experiment are as follows: Fig.16 Middle A, Fig.16 B in the figure is the normalized single-molecule force spectroscopy data. The sample is PS-PMAA fixed on a silicon wafer treated with dendrimers. According to statistics, the breaking force is 2.4±0.2nN. Compared with Example 1, there is almost no difference in the connection strength, which proves that for PS-PMAA molecules, the interface connection strength of 2.4nN can also be achieved, proving that this scheme is also applicable to other polymer molecules and organic solvent environments (N,N-dimethylacetamide, previous experiments on carboxymethyl starch were collected from aqueous solution environments).

[0250] Example 2 proves that the scheme of using parallel covalent bonds is not limited to aqueous solution environments, but can also improve the connection strength of the polymer-inorganic material interface in organic solution environments.

[0251] Example 8 Lifespan of a single molecule on a silicon wafer under high stress conditions

[0252] PBS buffer containing carboxymethyl starch (20 mg / mL), EDC (20 mg / mL) and NHS (20 mg / mL) was added dropwise to the silicon wafer surface functionalized by Scheme 4 and allowed to stand for 30 minutes to allow the carboxymethyl starch to form a stable covalent connection with the silicon wafer surface;

[0253] The silicon wafer connected with carboxymethyl starch was rinsed with PBS buffer and mounted in an atomic force microscope for single-molecule force spectroscopy experiments. The atomic force microscope probe used was the silicon nitride probe functionalized in Example 4.

[0254] In the single-molecule force spectroscopy experiment, the spring constant of each cantilever beam was calibrated in an underwater (PBS buffer) environment using the thermal noise method, and the obtained spring constant was 0.02-0.12 N / m. All single-molecule force spectroscopy experiments were performed in PBS buffer;

[0255] During the reciprocating stretching experiment, the atomic force microscope silicon nitride probe first contacts the silicon wafer connected with carboxymethyl starch. After the atomic force microscope silicon nitride probe forms a covalent connection with the carboxymethyl starch, the silicon nitride probe tip is controlled to retract from the silicon wafer. During the retraction process, the molecular bridge formed between the silicon nitride probe and the silicon wafer can be stretched. After the carboxymethyl starch molecules are stretched to a certain internal stress (or a certain length), further stretching is stopped. After the probe is controlled to maintain the current height for 1 second, it begins to approach the silicon wafer again. The probe is controlled not to contact the surface of the silicon wafer. After the stretched molecular bridge is completely relaxed, the stretching behavior is performed again. This process is repeated until the molecular bridge can no longer withstand the internal stress and breaks. The experiment ends. The schematic diagram of the experiment is shown in FIG. Fig.17 A, for the reciprocating tensile test, the typical force signal obtained is as follows Fig.17 In B, first, a single molecular bridge can sustain nearly 500 stretching cycles without breaking, showing strong stability. Fig.17 In Figure C), it can be observed that the intramolecular stress has reached a level above 1.8 nN, and it can be maintained at this high stress level for 50 cycles without breaking. Compared with the literature reports, the polymer-interface connection mode of non-parallel covalent bonds on the silicon surface can only be maintained at a stress level of 1 nN for less than 0.1 second.

[0256] In the force clamp experiment, the atomic force microscope silicon nitride probe first contacts the silicon wafer connected with carboxymethyl starch. After the atomic force microscope silicon nitride probe forms a covalent connection with the carboxymethyl starch, the silicon nitride probe tip is controlled to retract from the silicon wafer. During the retraction process, the molecular bridge formed between the silicon nitride probe and the silicon wafer can be stretched. When the carboxymethyl starch molecules are stretched to a certain internal stress (or a certain length), further stretching is stopped, and the current force level is controlled to remain unchanged by slightly adjusting the probe height until the life of the weak link inside the molecular bridge is reached, and the experiment is ended. Or, when the preset dwell time ends, the probe is actively controlled to move upward to break the molecular bridge and end the experiment. The experimental schematic diagram is shown in the figure. Fig.18 A, for the force clamp experiment, the typical force signal obtained during the probe dwell phase is shown in Figure 2. Fig.18 Middle B, Fig.18 Figure C in the middle is the complete force-time curve during the force clamp process. Experimental data show that a single molecular bridge can be maintained at a stress level of 1.81nN for more than 20 seconds, also achieving an extremely long life under high stress conditions.

[0257] Example 9 Patterned Mechanochemical Initiation of Quartz Slice Surface

[0258] A PBS buffer solution containing succinic acid (40 mg / mL), EDC (200 mg / mL) and Sulfo-NHS (200 mg / mL) was added dropwise to the surface of the quartz plate functionalized in Example 4, and allowed to stand for 30 minutes to allow the succinic acid to form a stable covalent connection with the surface of the quartz plate;

[0259] The PDMS nanostamp functionalized in Example 5 was pressed onto the surface of the quartz plate modified with succinic acid, and a pressure of 20 N was applied for 30 minutes to form a stable covalent connection between the two interfaces;

[0260] The PDMS nanostamp was then vertically peeled off the quartz slide surface to induce the force-promoted hydrolysis reaction of the interfacial amide bonds;

[0261] After the PDMS nanostamp and quartz sheet were peeled off, the surface chemical bonds were calibrated using aminofluorescein and carboxyl fluorescent microspheres, respectively. Finally, the fluorescent structure of the surface pattern was determined by fluorescence microscopy and atomic force microscopy. The flow chart is shown in the figure. Fig.19 , the results are shown in Fig. 20 , the fluorescence microscope imaging results showed that a fluorescent stripe with a width of 300nm appeared on the surface of the PDMS nanostamp after being soaked in aminofluorescein solution, and a nano fluorescent stripe with a consistent structure appeared on the quartz sheet after being soaked in carboxyl fluorescent microspheres, EDC, and NHS solutions. Furthermore, through AFM imaging, a regular arrangement structure of fluorescent microspheres can be observed on the surface of the quartz sheet. Correspondingly, in Control Example 3, no fluorescent stripe appeared. This proves that through the parallel covalent bond method, the target functional group (such as the amino group in Example 4) can be generated on the surface of the inorganic material by nanoimprinting.

[0262] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be regarded as the protection scope of the present invention.

Claims

1. A method for enhancing the connection strength of a gold-polymer interface, characterized in that: The following steps are involved: Functionalizing gold to obtain functionalized gold, wherein the functionalization is hydroxylation; The functionalized gold is reacted with a compound to form a parallel covalent bond, the compound is a dendron-shaped molecule, and the reaction is an esterification reaction; The dendron-shaped molecule has a structure shown in Formula I: Formula I; The hydroxylation comprises the following steps: immersing the gold in a solution of a compound containing both a hydroxyl group and a thiol group to obtain hydroxyl-modified gold; The hydroxyl-modified gold is mixed with the dendritic molecule for esterification reaction, and the obtained esterification product is mixed with trifluoroacetic acid to remove the CBZ protecting group of the amino group, wherein the CBZ protecting group has a structure shown in Formula II: Formula II, In the formula II, * represents a connection site.

2. A method for enhancing the connection strength of a gold-polymer interface, characterized in that: The following steps are involved: Functionalizing gold to obtain functionalized gold, wherein the functionalization is carboxylation; reacting the functionalized gold with a compound to form a parallel covalent bond, wherein the compound is a dendrimer molecule, and the reaction is an amidation reaction; The dendritic molecule is a PAMAM dendritic polymer, CAS No. 153891-46-4; The carboxylation comprises the following steps: immersing the gold in a solution of a compound containing both carboxyl and thiol groups; The compound containing both carboxyl and thiol groups includes mercaptoundecanoic acid, 6-mercaptohexanoic acid or 8-mercaptooctanoic acid, to obtain carboxyl-modified gold; The carboxyl-modified gold is mixed with dendrimers to undergo an amidation reaction.

3. A method for enhancing the connection strength of a silicon-polymer interface, characterized in that: The following steps are involved: Functionalizing silicon to obtain functionalized silicon, wherein the functionalization is hydroxylation; The functionalized silicon reacts with a compound to form a parallel covalent bond, the compound is a dendron-shaped molecule, and the reaction is an esterification reaction; The dendron-shaped molecule has a structure shown in Formula I: Formula I; The hydroxylation comprises the following steps: immersing the silicon in a solution of 3-glycidyloxypropylmethyldiethoxysilane to carry out a silylation reaction to obtain epoxidized silicon; subjecting the epoxidized silicon to an acid-catalyzed ring-opening reaction to obtain alcoholic hydroxyl-modified silicon; The alcoholic hydroxyl-modified silicon is mixed with a dendritic molecule for esterification reaction, and the obtained esterification product is mixed with trifluoroacetic acid to remove the CBZ protecting group of the amino group, wherein the CBZ protecting group has a structure shown in Formula II: Formula II, In the formula II, * represents a connection site.

4. A method for enhancing the connection strength of a silicon-polymer interface, characterized in that: The following steps are involved: Functionalizing silicon to obtain functionalized silicon, wherein the functionalization is carboxylation; The functionalized silicon reacts with a compound to form a parallel covalent bond, the compound is a dendritic molecule, and the reaction is an amidation reaction; The dendritic molecule is a PAMAM dendritic polymer, CAS No. 153891-46-4; The carboxylation comprises the following steps: soaking the silicon in a solution of carboxyethylsilanol sodium salt to obtain carboxyl-modified silicon; The carboxyl-modified silicon is mixed with a dendrimer to undergo an amidation reaction.

5. A method for enhancing the quartz-polymer interface connection strength, characterized in that: The following steps are involved: Functionalizing quartz to obtain functionalized quartz, wherein the functionalization is carboxylation; The functionalized quartz reacts with a compound to form a parallel covalent bond, the compound is a dendrimer molecule, and the reaction is an amidation reaction; The dendritic molecule is a PAMAM dendritic polymer, CAS No. 153891-46-4; The carboxylation comprises the following steps: immersing the quartz in a solution of carboxyethylsilanol sodium salt to obtain carboxyl-modified quartz; The carboxyl-modified quartz is mixed with dendrimer molecules to undergo an amidation reaction.

6. A method for enhancing the interfacial bonding strength of polydimethylsiloxane-polymer, characterized in that: The following steps are involved: Functionalizing polydimethylsiloxane to obtain functionalized polydimethylsiloxane, wherein the functionalization is epoxidation; The functionalized polydimethylsiloxane reacts with a compound to form a parallel covalent bond, the compound is a dendritic molecule, and the reaction is an addition reaction; The dendritic molecule is a PAMAM dendritic polymer, CAS No. 153891-46-4; The epoxidation comprises the following steps: coating 3-glycidyloxypropylmethyldiethoxysilane on the surface of the polydimethylsiloxane for epoxidation reaction to obtain epoxy-modified polydimethylsiloxane; The epoxy-modified polydimethylsiloxane is mixed with the dendritic molecule to carry out an addition reaction.

Citation Information

Patent Citations

  • Amino-modified chip, preparation method therefor and use thereof

    WO2022033453A1